Sensorimotor Control for Manipulating A Glass of Water-Effects of Visual and Tactile Feedbacks - Lin, Leitong; Li, Ke; Yue, Shouwei; Tian, Xincheng; Wei, Na (International Conference on Signal Processing (Print), 2018)
This study aimed to examine the effects of visual and tactile feedback on kinematic performance during manipulation of a glass of water. Twelve healthy subjects were instructed to reach, grasp and lift a glass of water, and then pour the water into another glass without spilling out. Two visual conditions (vision vs. non-vision) and two tactile feedbacks with different object's weight (200 ml vs. 400 ml water inside the glass). Kinematic signals of the hand and glass were recorded using a motion capture system. The movement trajectory of manipulation was divided into three phases (lifting phase-LP, pouring phase-PP and replacing phase-RP). The duration of each phase (Duration) and the rate of change of the deflection angle (CDA) were extracted as parameters. For Duration parameter, the results showed that grasping a heavy versus light glass had significant different Duration of PP (p < 0.05) for either vision or non-vision condition. Neither the LP nor PP showed any significant differences in Duration between the light and heavy conditions, or between the visual and non-visual conditions. About the CDA parameter, we found that for the right hand without visual feedbacks, grasping a heavy glass in both LP and PP showed significantly lower CDA than grasping a light glass (p < 0.05); by contrast, with visual feedbacks a significant difference was only observed in CDA of PP between the light and heavy conditions (p < 0.05). For the left hand, the CDA was significantly affected by weight in LP and PP under both visual and non-visual conditions (p < 0.05). These findings may help us to better understand the effects of vision and tactile sensation on dexterous manipulation and may facilitate evaluation of hand sensorimotor deficits.